Karakteristik Bahasa Arab dan Relevansinya dalam Konteks Pendidikan Bahasa Asing - kiki irawan; Nevy Agustina; Zulhannan, Zulhannan; Ghazi, Fachrul; Hijriyah, Umi (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
Arabic is a Semitic language that has a complex and rich linguistic structure, both in terms of phonology, morphology, syntax, and semantics. This complexity makes it unique compared to many other languages ​​in the world, as well as challenging to learn as a foreign language. In the context of foreign language education, a deep understanding of the characteristics of the Arabic language is essential to design effective and adaptive learning strategies. This article aims to describe the main characteristics of the Arabic language and evaluate the extent to which these characteristics are relevant in the context of teaching a foreign language to non-Arabic speakers. This study uses a qualitative-descriptive approach through a literature study of various relevant scientific sources. The results of the analysis show that the Arabic phonological system, which includes unique letters such as ح، ع، ق, as well as a root-based and pattern-based morphological system (wazn), presents its own challenges in learning. However, the system also opens up pedagogical opportunities through a pattern-based and context-based approach. In addition, the flexible syntactic structure and rich semantic meaning of Arabic demand contextual and communicative teaching strategies. This article concludes that understanding the characteristics of Arabic is not only important for overcoming learning difficulties, but can also be used to strengthen the effectiveness of learning Arabic as a foreign language